Exploring Mangrove Potential for Heavy Metal Phytoremediation Along Coastal Zones: A Study of Sempu Island Nature Reserve - Alfin Fatwa Mei Afifudin; Rony Irawanto; Hari Purnomo (Universitas Airlangga, 2023)
Sempu Island Nature Reserve (CAPS) in East Java is one of the nature reserves in Indonesia. On this island, there are various native Indonesian vegetation, including mangroves. One of the biological functions of mangrove plants is as a shelter for marine species, wave breaker, and as a phytoremediator to prevent water pollution. This research is an exploratory study that aims to discover the diversity of mangrove species on Sempu Island and evaluate their potential as heavy metal phytoremediator using the literature review method. The exploration was conducted in July 2022 on three different locations on Sempu Island, which are Semut Bay, Ra'as Bay, and Freshwater area. In conclusion, eight species have been identified as true mangrove species in Sempu Island Nature Reserve, East Java. Such as Aegiceras corniculatum, Ceriops decandra, Exoecaria agallocha, Heritiera littoralis, Rhizophora apiculate, Rhizophora mucronata, Rhizophora stylosa, and Xylocarpus granatum, which originate from five families and six genera. Furthermore, Ceriops decandra has a conservation status of